2014
DOI: 10.2147/ijn.s58942
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow test strip based on colloidal selenium immunoassay for rapid detection of melamine in milk, milk powder, and animal feed

Abstract: Although high melamine (MEL) intake has been proven to cause serious health problems, MEL is sometimes illegally added to milk products and animal feed, arousing serious food safety concerns. A satisfactory method of detecting MEL in onsite or in-home testing is in urgent need of development. This work aimed to explore a rapid, convenient, and cost-effective method of identifying MEL in milk products or other food by colloidal selenium-based lateral flow immunoassay. Colloidal selenium was synthesized by L-asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…This is consistent with other colloidal gold LFIAs that have demonstrated reliability up to one year. 31 , 32 This stability allows for strips used at the point-of-care to undergo reevaluation at a centralized laboratory for quality assurance.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other colloidal gold LFIAs that have demonstrated reliability up to one year. 31 , 32 This stability allows for strips used at the point-of-care to undergo reevaluation at a centralized laboratory for quality assurance.…”
Section: Resultsmentioning
confidence: 99%
“…86 Dinitrobutylphenol is very detrimental to human and aquatic animals as it has carcinogenicity. Dinitrobutylphenol is released in to waste water causing environmental pollution, SeNPs based chemiluminescence system is, so far, best for its detection.…”
Section: Iii) Sensormentioning
confidence: 99%
“…Selenium nanoparticles are prepared at room temperature, easily bind to proteins, and are not sensitive to electrolytes. They also have higher levels of sensitivity, and are more economical to prepare than other probe types [19]. The current study is based on our reported article on how to prepare selenium nanoparticles [18].…”
Section: Introductionmentioning
confidence: 99%